Gambaran Keadaan Fasilitas Sanitasi Di Pasar Kreneng Desa Dangin Puri Kangin Kecamatan Denpasar Utara Tahun 2021 - Sintiya Marisa; Anysiah Elly Yulianti; Ni Ketut Rusminingsih (Jurnal Kesehatan Lingkungan (JKL), 2021)
Poor market sanitation conditions can indirectly affect the health of the market occupants. This research was conducted at Kreneng Market, while this research was to describe the state of sanitation facilities in Kreneng Market including the state of clean water, the state of bathrooms and toilets, waste management, the state of the waste water disposal facilities, the state of the hand washing area and efforts to control vectors and infectious animals. disease. The research used a descriptive method with the results of this study, namely the state of clean water, the state of the bathroom and toilet, the state of SPAL, the state of the washing place which were categorized as having met the requirements in accordance with Permenkes No. 17 of 2020, while waste management and efforts to control vectors and animals that transmit diseases are categorized as not meeting the requirements. The suggestions that the author wants to give, namely the Kreneng Market managers are expected to maintain the state of clean water, state of the bathrooms and toilets, waste management, state of waste water disposal facilities, state of hand washing and control efforts of vectors and disease-transmitting animals, if possible to be improved again. To the traders in Kreneng Market, the author hopes to jointly with the market managers maintain the cleanliness of the market sanitation facilities